Immunochip analysis identifies association of the RAD50/IL13 region with human longevity. Issue 3 (22nd March 2016) - Flachsbart, Friederike; Ellinghaus, David; Gentschew, Liljana; Heinsen, Femke‐Anouska; Caliebe, Amke; Christiansen, Lene; Nygaard, Marianne; Christensen, Kaare; Blanché, Hélène; Deleuze, Jean‐François; Derbois, Céline; Galan, Pilar; et al.
Summary: Human longevity is characterized by a remarkable lack of confirmed genetic associations. Here, we report on the identification of a novel locus for longevity in the RAD50/IL13 region on chromosome 5q31.1 using a combined European sample of 3208 long‐lived individuals (LLI) and 8919 younger controls. First, we performed a large‐scale association study on 1458 German LLI (mean age 99.0 years) and 6368 controls (mean age 57.2 years) by targeting known immune‐associated loci covered by the Immunochip. The analysis of 142 136 autosomal single nucleotide polymorphisms (SNPs) revealed an Immunochip‐wide significant signal ( P I mmunochip = 7.01 × 10 –9 ) for the SNP rs2075650 in the TOMM40 / APOE region, which has been previously described in the context of human longevity. To identify novel susceptibility loci, we selected 15 markers with P I mmunochip < 5 × 10 –4 for replication in two samples from France (1257 LLI, mean age 102.4 years; 1811 controls, mean age 49.1 years) and Denmark (493 LLI, mean age 96.2 years; 740 controls, mean age 63.1 years). The association at SNP rs2706372 replicated in the French study collection and showed a similar trend in the Danish participants and was also significant in a meta‐analysis of the combined French and Danish data after adjusting for multiple testing. In a meta‐analysis of all three samples, rs2706372 reached a P ‐value of P I mmunochip+Repl = 5.42 × 10 −7 (OR = 1.20; 95% CI = 1.12–1.28). SNP rs2706372 is located in the extended RAD50/IL13 region. RAD50 seems a plausible longevity candidate due to its involvement in DNA repair and inflammation. Further studies are needed to identify the functional variant(s) that predispose(s) to a long and healthy life.